2014
DOI: 10.3329/icpj.v3i6.18760
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic and phytochemical investigation of young leaves of Triticum aestivum Linn.

Abstract: The aim of the work is to perform the pharmacognostic study of the leaves of plant Triticum aestivum Linn., Family Poaceae, commonly known as ‘Wheatgrass’. It is cultivated on large scale all over India and also occasionally cultivated in garden. For the present study samples of the Wheatgrass leaves were collected over a specific period of nine days. The drug was cultivated with specific type of hybrid seeds obtained from most reputed institution of India and were scrupulously analysed. For standardization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As documented literature shows that alkaloids are most active phytoconstituents against various bacterial strains and act differently due to the difference in chemical composition of cell membrane (Lewis and Ausubel, 2006). The crude extract of T. aestivum showed good inhibition zone against all mastitis pathogens and showed similar results to the Jain and Argal (2014). Various studies reported the presence of bioactive phytochemicals like alkaloids; proteins, carbohydrates, phenolics, glycosides, tannins, fibers and saponins in this plant are responsible for their antimicrobial potential (Jain and Argal, 2014).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As documented literature shows that alkaloids are most active phytoconstituents against various bacterial strains and act differently due to the difference in chemical composition of cell membrane (Lewis and Ausubel, 2006). The crude extract of T. aestivum showed good inhibition zone against all mastitis pathogens and showed similar results to the Jain and Argal (2014). Various studies reported the presence of bioactive phytochemicals like alkaloids; proteins, carbohydrates, phenolics, glycosides, tannins, fibers and saponins in this plant are responsible for their antimicrobial potential (Jain and Argal, 2014).…”
Section: Discussionmentioning
confidence: 71%
“…The crude extract of T. aestivum showed good inhibition zone against all mastitis pathogens and showed similar results to the Jain and Argal (2014). Various studies reported the presence of bioactive phytochemicals like alkaloids; proteins, carbohydrates, phenolics, glycosides, tannins, fibers and saponins in this plant are responsible for their antimicrobial potential (Jain and Argal, 2014). These results provide scientific proof not only for the nutritional value of wheat but also for its medicinal value and various pharmacological activities.…”
Section: Discussionmentioning
confidence: 71%
“…Recently numbers of natural and synthetic drugs have been reported for symptomatic treatments. [20][21][22][23][24][25][26][27][28][29] Numerous drug design studies have been reported for search of novel compounds. [30][31][32][33][34][35][36][37][38] Numbers of novel drug delivery systems have been utilizes for effective drug delivery.…”
Section: Treatment Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Z. xylopyra [10]. The phytochemical screening of Z. xylopyrus leaves extract with various solvents showed the presence of alkaloids, carbohydrates, steroids and sterol, glycosides, saponins, flavonoids, phenolic compounds, triterpenoids [11][12][13].…”
Section: Introductionmentioning
confidence: 99%